Aktualisasi Program Healthy Schools Dalam Membentuk Kepedulian Peserta Didik Di SMP Muhammadiyah Plus Klaten Utara - Shindid Gunagraha (PT PUBLIKASI INSPIRASI INDONESIA, 2025)
The research aims to examine of the healthy school program through the environment and habituation of activities at school as a learning medium for students in the formation of various aspects of knowledge, attitudes, and skills. In addition, to the implementation in creating a healthy school program in shaping attitudes or caring characters at Muhammadiyah Plus Junior High School Klaten, the implementation of healthy schools by providing active understanding to students is then implemented in the schedule of activities at school. So that a healthy school becomes a medium for learning character or caring attitudes for students so that they can get used to it and make good habits in their environment. This study uses qualitative field research, a research site at Muhammadiyah Plus Junior High School Klaten.. The results of the discussion showed that there were findings of creating a healthy school program, one of which was interesting through nutritious eating activities for students, what was interesting was the independence and level of concern of students after spending food by washing and sorting garbage and disposing of garbage in the designated place. The conclusion is that through the habituation of activities that support the healthy school program, it will create a conducive, comfortable, and healthy learning environment for learning at school.